2020
DOI: 10.1177/2051415820903192
|View full text |Cite
|
Sign up to set email alerts
|

Frozen section analysis for organ-conserving surgery in penile cancer: Assessing oncological outcomes and trends of local recurrence

Abstract: Introduction and objectives: The local recurrence rate of penile cancer following surgical excision is reported in many series to be between 6 and 29%. Intra-operative frozen section (FS) is a useful tool to ensure safe microscopic margins in organ-sparing procedures in penile cancer. In this series, we assessed the rates of positive margins and patterns of local recurrence in a multicentre cohort of patients undergoing penile-preserving surgery assisted by intra-operative FS analysis. Materials and methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A diagnosis of cancer was confirmed in all cases by biopsy. The use of intraoperative frozen sections ensured that oncological clear margins were achieved when treating the primary [ 8 ]. All data collected on the MRI report with the corresponding final histopathology was anonymised, with patient-identifiable information removed before being reviewed and analysed by the researcher.…”
Section: Methodsmentioning
confidence: 99%
“…A diagnosis of cancer was confirmed in all cases by biopsy. The use of intraoperative frozen sections ensured that oncological clear margins were achieved when treating the primary [ 8 ]. All data collected on the MRI report with the corresponding final histopathology was anonymised, with patient-identifiable information removed before being reviewed and analysed by the researcher.…”
Section: Methodsmentioning
confidence: 99%
“…However, this examination is labour intensive, requiring an available histopathologist, is time consuming, and is not 100% accurate in its assessment. A recent study has suggested that the use of FFS may reduce recurrence rates [11,12].…”
Section: New Ways Of Determining Resection Marginsmentioning
confidence: 99%